Hypoxia Onset in Mesenchymal Stem Cell Spheroids: Monitoring With Hypoxia Reporter Cells - Schmitz, Carola; Potekhina, Ekaterina; Irianto, Teresa; Belousov, Vsevolod V.; Lavrentieva, Antonina (Frontiers in Bioengineering and Biotechnology, 2021)
The bioregenerative potential of human mesenchymal stems cells (hMSCs) makes these cells a promising candidate for cellular therapies and tissue engineering. On the path of a successful medical application of hMSC, the cultivation of cells in a three-dimensional (3D) environment was a landmark for the transition from simple two-dimensional (2D) testing platforms to complex systems that mimic physiological in vivo conditions and can improve hMSC curative potential as well as survival after implantation. A 3D arrangement of cells can be mediated by scaffold materials where cells get entrapped in pores, or by the fabrication of spheroids, scaffold-free self-organized cell aggregates that express their own extracellular matrix. Independently from the cultivation method, cells expanded in 3D experience an inhomogeneous microenvironment. Many gradients in nutrient supply, oxygen supply and waste disposal from one hand mimic in vivo microenvironment, but also put every cell in the 3D construct in a different context. Since oxygen concentration in spheroids is compromised in a size-dependent manner, it is crucial to have a closer insight on the thresholds of hypoxic response in such systems. In this work, we want to improve our understanding of oxygen availability and consequensing hypoxia onset in hMSC spheroids. Therefore we utilized human adipose tissue-derived MSCs (hAD-MSCs) modified with a genetical sensor construct to reveal (I) the influence of spheroid production methods and (II) hMSCs cell number per spheroid to detect the onset of hypoxia in aggregates. We could demonstrate that not only higher cell numbers of MSCs, but also spheroid formation method plays a critical role in onset of hypoxia.